Livestock fattening innovation in Ethiopia—The Metema story - International Livestock Research Institute (International Livestock Research Institute, 2012)
This video documents how a 2005 alliance between the local government office of agriculture, the IPMS project, and local livestock farmers and traders in western Ethiopia took advantage of livestock market opportunities in neighbouring Sudan. Through dialogue with local actors, the team worked out a "new way of doing business." This brought knowledge to farmers, connected them to animal health providers, encouraged shopkeepers to sell feed for fattening, and reached out to farmers through community institutions like the church. What went right in Metema? First, farmers were empowered through sharing of new ideas - on fattening and on market opportunities. Second, the team addressed issues beyond production, reaching out to input providers and others. Third, the team worked with farmers and input suppliers who volunteered to try fattening, with their own resources. Some of the critical building blocks to sustain and scale out this approach include: Effective partnerships among all actors in the value chain; appropriate knowledge for farmers on many topics; stronger input supply systems; stronger support systems for farmers to get hold of services; market information